Comparing the monochromatic TL response of a high sensitivity natural quartz irradiated with β and γ rays (Brazilian Journal of Radiation Sciences (BJRS), 2022)
This study investigates the effect of the dose-rate in the thermoluminescent glow curves of a single crystal of quartz. The samples were sensitized by the γ radiation combined with the heat-treatments. The glow curves were registered in zeroed (unsensitized) and sensitized conditions using an optical filter centered in violet spectral region. Tens mGy test doses were administered with one β (90Sr/90Y) source and two γ radiation sources (60Co and 137Cs). The TL curves were deconvoluted using a first-order kinetic model. Differences in the glow curves and trapping parameters were observed between zeroed and sensitized samples. Differences were found in the TL curves comparing the three radiation sources. The principal variation is the remarkable increase in the TL signal above 350 °C, which is observed only in sensitized samples with the minor dose-rate source (137Cs). This signal seems to be associated with deep trapping states. The intensities of the components defining the first peak and the high temperature signal show a dependence on the dose-rate. The dose-rate dependence of the first-peak components is explained by the competing effects that may take place during the excitation stage. The components that fitted the sensitized peak (260 oC) do not exhibit a clear dependence on the dose-rate of radiation source.